P43. Dysphagia and difficulties with tablet intake in ALS – Assessment from the patient perspective. Issue 8 (August 2018) - Maier, A.; Spittel, S.; Funke, A.; Kettemann, D.; Münch, C.; Meyer, T.
Abstract : Background: Dysphagia is a frequent and severe symptom in amyotrophic lateral sclerosis (ALS) (Onesti et al., 2017 ).It disturbs nutrition and medication intake and leads to aspiration of liquids as well as solid substances.Dysphagia frequently results in unintended weight loss and may require the use of percutaneous endoscopic gastrostomy (PEG). Although dysphagia and PEG are known barriers for tablet intake in ALS, few systematic investigations have been reported so far. Methods: 650 patients with ALS, who participated in an ALS-centered case management program (Ambulanzpartner) and were registered on the program-related case management platform (Ambulanzpartner-Versorgungsportal; www.ambulanzpartner.de) were invited to answer a survey about ALS-related dysphagia.203 patients (31%) conducted an online self-assessment ( n  = 97; 48 %) or were interviewed via telephone ( n  = 106; 52%).The assessment was carried out between December 2016 and February 2017. Results: Dysphagia was reported by 61% ( n  = 123) of ALS patients.In 21% ( n  = 42) severe dysphagia necessitated the use of PEG (Fig.1 ).41% of participants ( n  = 84) experienced difficulties with tablet intake, which was reported as sticking at palate and tongue, melting in mouth, irritation of the throat, and fear of choking.In 27% ( n  = 55) tablet intake was impossible due to dysphagia (Fig.2 ).These patients reported an inappropriate crushing of medication for oral intake or administration of the crushed tablets via PEG tube. Conclusion: Dysphagia and difficulties with tablet intake occurs frequently in patients with ALS. Crushing tablets was shown to be a 'routine' practice to overcome dysphagia-related difficulties of tablet intake although the grinding of tablets poses the risks of reduced bioavailability, of tube obstruction and of unwanted drug interactions – if different crushed tablets are given at once.The results of this assessment underline the importance of liquid formulations and suspensions of ALS-related drugs to ensure a save and appropriate administration of medicines during the course of ALS. Acknowledgements: This work was supported by a grant ofDESITIN Arzneimittel GmbH to Ambulanzpartner Soziotechnologie GmbH. Conflicts of interest: TM and CM are founders of the internet platform Ambulanzpartner and hold shares of Ambulanzpartner Soziotechnologie GmbH.